(untitled) (Olhar de Professor, 2022)
This article aims to analyze the perceptions of undergraduate students about the use of online platforms as a collaborative learning environment and its relevance to the formative processes in the molds of Education 3.0. This is an excerpt from a Master’s thesis in Education in the area of technology and education, which had as its research practice the use of social networks as a learning environment, developed in the Portuguese Instrumental discipline, of the undergraduate course in Vernacular Letters of a federal university. The research, with a qualitative approach, had as subjects the seventeen students of the discipline and was carried out through the Research-formation method, using participant observation, the questionnaire and the semi-structured interview as instruments of data collection, the latter carried out only with graduating students in the class. The data showed the need to reflect on the practices necessary for teaching today, highlighting, based on the testimonies of the participants, the absence in the initial formation of more dynamic activities and practices, in which there is effective use of technologies, which culminates in insecurity about future challenges. If the student is in the process of training, regardless of the chosen professional destinations, it is necessary to link teaching to the practices that take place in the computerized and interconnected society in which we live.